Persepsi Tokoh Agama tentang Pernikahan Dini: Kajian Kualitatif dalam Perspektif Hukum Islam - Harahap, Ahmad Rofii; Sehoni, Sehoni (EL-EMIR Institute, 2025)
This study aims to examine the perceptions of religious leaders toward the practice of early marriage from the perspective of Islamic law. The phenomenon of early marriage remains prevalent in various regions, and religious leaders play a significant role in shaping public opinion and influencing community decisions on the matter. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with several religious figures (including ulama, ustadz, and marriage registrars) in selected areas with relatively high rates of early marriage. The data analysis technique was conducted using a qualitative descriptive approach, which included data reduction, data presentation, and conclusion drawing. The findings indicate that religious leaders' perceptions of early marriage vary. Some consider early marriage to be religiously permissible (shar’i) if it meets the required conditions and pillars of marriage and is based on public benefit, particularly in preventing promiscuity. However, others emphasize the importance of age maturity, mental preparedness, and long-term welfare considerations, leading them to generally discourage early marriage. Overall, religious leaders agree that early marriage should be viewed contextually, not solely based on biological age, but also by considering psychological, social, and applicable legal aspects in Indonesia.